Independent or Integrated Plastic Surgery Residency Pathways: Trends in Representation in Academic Plastic Surgery in the United States. Issue 4 (28th October 2021) - Erpenbeck, Sarah P.; Bustos, Samyd S.; Smith, Brandon T.; Egro, Francesco M.; Nguyen, Vu T.
Abstract : Introduction: The training pathway for plastic surgery has evolved in recent years with the adoption and rise in popularity of the integrated model. Studies have demonstrated that there may be differences between integrated graduates and independent graduates, specifically in career choices and type of practice. This study seeks to understand if there are differences in representation at academic and leadership positions between graduates of the 2 pathways. Methods: A cross-sectional study was conducted in June of 2018 to assess integrated and independent pathway graduate's representation in academic plastic surgery in the United States. Factors examined were career qualifications, academic productivity, faculty positions, and influence of pathway on career advancement. Results: A total of 924 academic plastic surgeons were analyzed, 203 (22.0%) of whom were integrated graduates and 721 (78.0%) of whom were independent graduates. Independent graduates had greater National Institutes of Health funding (integrated, 40, 802; independent, 257, 428; P = 0.0043), higher h -index (integrated, 7.0; independent, 10.0; P < 0.001), and higher publication number (integrated, 17; independent, 25; P = 0.0011). Integrated graduates were more likely to be assistant professors (integrated, 70%; independent, 40.7%; P < 0.001) and required a shorter postresidency time to reach all positions examined compared with independent graduates. Conclusions: Residency training pathway influences academic plastic surgeons in research output, qualifications, and academic positions. This is likely due to the relatively new nature of the integrated program compared with the independent, as well as the shorter length of training for integrated graduates. However, trends are moving toward integrated graduates showing increased interest and productivity in academic medicine.